Synthesis and biological evaluation of some heterocyclic compounds - Mohamed, Meena Allab; Mohamed, Yassin; Eid, Nahed M.; Barsoum, Flora F. (Journal of Applied Pharmaceutical Research, 2018)
Cancer is one of the most striking diseases that has a potential impact on human health with high mortality rate. During the last century many anticancer agents have emerged but unfortunately, these agents could not provide effective solutions for cancer treatment due to side effects and resistance. All over the world, asking for new anticancer agents is still a major goal for medicinal chemists. Pyrrole and pyrrolo[2,3-d]pyrimidine scaffolds are very interesting bioactive core exhibiting several biological activities as anticancer, anti-inflammatory, antimicrobial activities. Herein, we highlighted on the anticancer activity of the pyrrole and pyrrolo[2,3-d]pyrimidine derivatives which are reported to possess anticancer activity and many of them are in market or still in clinical trials. This work deals with design and synthesis of new pyrrole and pyrrolopyrimidine derivatives. The new compounds were screened for their cytotoxic activity against HepG2 and MCF7in vitro. The most active compounds were evaluated for their VEGFR-2 inhibition in vitro